Assessment of vinyl chloride-induced DNA damage in lymphocytes of plastic industry workers using a single-cell gel electrophoresis technique - Awara, Wageh M; El-Nabi, Sobhy H; El-Gohary, Mona (Toxicology (Amsterdam), 1998)
DNA damage and the formation of stable carcinogen–DNA adducts are considered critical events in the initiation of the carcinogenic process. This study was carried out to assess whether exposure of plastics industry workers to the vinyl chloride monomer (VCM) for different periods of time would cause DNA damage, using the single-cell gel electrophoresis (SCGE) technique. Levels of DNA damage was assessed by both extent of DNA migration and numbers of DNA damaged spots in the peripheral blood lymphocytes from 32 plastics workers with different periods of exposure to VCM; they were evaluated by comparison with a group of non-exposed individuals. It was found that plastics workers who were exposed to VCM for different periods of time showed significantly increased levels of DNA damage compared with the non-exposed subjects. There was a significant correlation between the severity of DNA damage and duration of exposure. However, no significant correlation was found between the age of all subjects and DNA damage. Concentrations of VCM in the air inside the factory were found to be significantly higher than values in non-exposed areas, despite being lower than the threshold limit value (TLV). Our results encourage the application of SCGE as a sensitive, simple, fast and useful technique in the regular health screening of workers occupationally exposed to VCM (even at concentrations below the TLV) to assess the possibility of any DNA damage.